Some Suggestions about the Gravity Ropeway Working in the Kulu Valley - Vaishnav, M. N. (Indian Forester, 1971)
At present large quantity of timber is roped down in the Kulu Valley through Skyline Crane and Gravity Ropeway. The present system involves many breakdowns due to rather faster descent of load. A considerable amount of time and energy is wasted in bringing up the carriage before it can be reloaded and roped down. In the present paper an attempt is made to show how a use of additional set of track rope, hauling rope and a carriage, if geared up properly can increase the efficiency and bring about a considerable saving in the recurring cost. Through rough calculations it has been worked out that by installing an equipment worth Rs. 50,000 or so the cost of roping down by Gravity Ropeway can be brought down from Rs. 11.25 per m3 at present to about Rs. 9.25 or 8.75 per m3, thereby saving a sum of about Rs. 8,000 to 10,000 per installation.